EXPERIENCE RISING FROM QUARTER-LIFE CRISIS: A PHENOMENOLOGY STUDY - Alfaruqy, Muhammad Zulfa; Indrawati, Endang Sri (Faculty of Psychology, Universitas Diponegoro, 2023)
Early adulthood is a vulnerable period to various problems in life. Various problems have the potential to lead individuals, especially in early adulthood, to a quarter-life crisis. This study aimed to understand the experience of falling and rising (resilience) from a quarter-life crisis. A phenomenological approach was used and involved seven participants (three men and four women) aged 25-29 years who generally have completed undergraduate education and had suicidal intentions. Collecting data using in-depth interviews. The results show that the participants who had suicidal intentions perceived that their parents’ parenting style was authoritarian, indicated by the excessive demands received. Participants are responding to this demand by rebelling against their parents. Rebellion, failure at work, and the breakdown of relationships with lovers brought them to a slump. Participants lost their purpose in life, felt depressed, and got suicidal intentions. Insight in the form of regret and hope for the future becomes a turning point in life. Acceptance from parents, peer group social support, and professional assistance are important factors in the process of recovering from the quarter-life crisis. Participants who exceed a crisis show a harmonious relationship with their parents and the opposite sex and work with the support of various parties. This research has implications for the urgency of communication and harmonious relations in the early adulthood phase, especially emerging adulthood.